ANALYSIS OF PPPK SALARY AND INCOME SCHEME IN THE 2023 ASN BILL - Ramadha Yanti Parinduri; Umar Sako Baderan; Abdullah Mitrin; Rieneke Ryke Kalalo; Shohib Muslim (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The ASN Bill which was just passed by the DPR last month presents the concept of a new salary scheme for PPPK. Initially PPK and PNS had slightly different salary schemes, especially regarding pension guarantees which PPPK did not have. The presence of the newly passed ASN Law does not recognize the difference between PPK and PNS salaries. Therefore, this research aims to describe the differences in salary schemes that exist in the old and new ASN Laws. This research is qualitative research with a descriptive approach. The data used in this research is secondary data using a library approach collected using data collection methods, data selection, data reduction and drawing conclusions.